2019
DOI: 10.1007/s13157-019-01219-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Barrier Breaching on Wetland Ecosystems under the Influence of Storm Surge, Sea-Level Rise and Freshwater Discharge

Abstract: Coastal wetland ecosystems and biodiversity are susceptible to changes in salinity brought about by the local effects of climate change, meteorological extremes, coastal evolution and human intervention. This study investigates changes in the salinity of surface water and the associated impacts on back-barrier wetlands as a result of breaching of a barrier beach and under the compound action of different surge heights, accelerated sea-level rise (SLR), river discharge and rainfall. We show that barrier breachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…As Brotherton et al (2019a) Environmental modelling provides an opportunity to explore potential impacts to vegetated communities under extreme events and sea level rise scenarios, and allows coastal management strategies to be tested. Li et al (2019) showed that a potential managed realignment at Minsmere, UK could result in the majority loss of freshwater reedbeds under even normal tidal conditions unless freshwater inputs were regulated. It is difficult to predict the precise impacts of new patterns of flooding on reedbeds and coastal wet grassland at Blakeney Freshes, given the complexities of flooding style (sudden peak v. gradual water inputs), final water depths and flood durations, and interactions between increased inundation, waterlogging and salinization (Spalding & Hester, 2007;Brotherton & Joyce, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As Brotherton et al (2019a) Environmental modelling provides an opportunity to explore potential impacts to vegetated communities under extreme events and sea level rise scenarios, and allows coastal management strategies to be tested. Li et al (2019) showed that a potential managed realignment at Minsmere, UK could result in the majority loss of freshwater reedbeds under even normal tidal conditions unless freshwater inputs were regulated. It is difficult to predict the precise impacts of new patterns of flooding on reedbeds and coastal wet grassland at Blakeney Freshes, given the complexities of flooding style (sudden peak v. gradual water inputs), final water depths and flood durations, and interactions between increased inundation, waterlogging and salinization (Spalding & Hester, 2007;Brotherton & Joyce, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Third, interventions to reverse the degradation and loss of coastal habitats—such as the managed realignment of low-lying shorelines—should be seen as experimental opportunities in which to learn more about how the biological–physical system works. Thus, for example, modelling of emergent wetland habitats following natural/artificial breaching of coastal defences points to the importance of the interactions between bed elevation (and its control of hydroperiod), hydrodynamics (in terms of both inputs (inlet morphodynamics) and outputs (drainage channel networks)) and sediment erosion/deposition, and also the role of vegetation cover and root depth/structure [ 20 ]. As the outcomes of these experiments emerge, it will be important to merge such interdisciplinary information with theory, observation, experiments and replication across systems, so as to establish generality and provide opportunity to minimize the time lag from theory through to evidence-based adoption in practice [ 21 ].…”
Section: Solutions and Ways Forward: Meeting The Challengementioning
confidence: 99%
“…These biomes are usually located in low altitude areas, and, because of that, they present direct contact with the ocean, being consequently disturbed by the flooding process. Li et al (2020) highlight that those losses due to the flooding process will be irreversible, if the RCP 8.5 scenario occurs, with diverse impacts, such as vegetation dieback and increase in salinity due to direct tidal flushing.…”
Section: Risk Of Flood Due Sea-level Risementioning
confidence: 99%